Combination of Nigella sativa and Phyllanthus niruri as An Immunostimulant for The Prevention of White Spot Disease in Litopenaeus vannamei - Wasmen Manalu; Min Rahminiwati; Muhammad Agus Suprayudi; Sri Nuryati; Wida Lesmanawati (Department of Aquaculture, 2022)
Pacific whiteleg shrimp (Litopenaeus vannamei) is a very important commodity, which accounts for almost 70% of the total world shrimp production. However, this production is still threatened by disease attacks, one of which is caused by white spot disease (WSD). Herbs are widely used as immunostimulants as an effort to prevent diseases. Black cumin (Nigella sativa) and stone breaker (Phyllanthus niruri) have long been known as excellent immunostimulants in human. This study aimed to evaluate the potential of N. sativa and its combination with P. niruri as an immunostimulant in L. vannamei for preventing WSD. Tested shrimp (±3.0 g) were treated by N. sativa (N), P. niruri (P) and the combination of both (1N:1P, 2/3N:1/3P, 3/4N:1/4P, 1/3N:2/3, 3/5N:2/5P, 1/4N: 3/4P, 2/5N:3/5P) through feed for 28 days. They were then infected by white spot syndrome virus (WSSV) and observed for 7 days. The parameters observed included immune response and production performance. N. sativa was able to reduce the mortality of test shrimp infected with WSSV, with an RPS value of 71%. N. sativa can be combined with P. niruri in the right composition (1/2N:1/2P and 2/3N:1/3P), while the other combinations are antagonistic. The administration of the best treatments in this study, relatively did not affect the value of total hemocyte count, phenoloxidase activity, respiratory burst activity, hemolymph clotting time and production performance of tested shrimp.